0=8-3(6-6x)

Simple and best practice solution for 0=8-3(6-6x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0=8-3(6-6x) equation:


Simplifying
0 = 8 + -3(6 + -6x)
0 = 8 + (6 * -3 + -6x * -3)
0 = 8 + (-18 + 18x)

Combine like terms: 8 + -18 = -10
0 = -10 + 18x

Solving
0 = -10 + 18x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-18x' to each side of the equation.
0 + -18x = -10 + 18x + -18x
Remove the zero:
-18x = -10 + 18x + -18x

Combine like terms: 18x + -18x = 0
-18x = -10 + 0
-18x = -10

Divide each side by '-18'.
x = 0.5555555556

Simplifying
x = 0.5555555556

See similar equations:

| .5y+(2x+5)=180 | | f(3)=12+3x | | s+8=-13.5 | | 4x-6x-7=7 | | 2x+9+7x-4=4x+7 | | 11x-154=-5x+54 | | 3(2y-3)=5(y+4) | | 30+8+7+10+25-4+9+25-3+6-5=108 | | x^2+2x-15=15 | | H+9.7=-9 | | x^3-2x^2-41x-56=0 | | 3xy+2x=4y | | 3(x+5)=6x+15 | | 4x+7=2x+9+7x-4 | | 4.1=d-5.1 | | 3.1x-1.6=5 | | 3=2x+1(x) | | (x)(x)+4x=117 | | 6(a+2b)+8b-16b= | | 5.6+z=3 | | 3x-2=130 | | 7-6y=31-4x | | 6x+6y=224.9 | | 5x+7+2x=4 | | 7x-8=4x-56 | | 2(8+p)= | | 4x+3x^2=7+5x | | X-7+3x-1=0 | | 6n=3n+42 | | -5x-31=7x+5 | | 6x+9=4x+39 | | -6+4x=5x+4 |

Equations solver categories